2003
DOI: 10.1038/sj.ijo.0802441
|View full text |Cite
|
Sign up to set email alerts
|

Weight development over time in parous women—The SPAWN study—15 years follow-up

Abstract: BACKGROUND: Weight gain is common after pregnancy. Most studies suggest that weight gain associated with a pregnancy is between 0.5 and 3.8 kg up to 2.5 y of follow-up. However, 73% of the female patients at our obesity clinic identified pregnancy as an important trigger for marked weight retention. The majority retained more than 10 kg after each pregnancy. The aim of this study was to examine long-term weight development after pregnancy in a 15 y follow-up of women who took part in the Stockholm Pregnancy An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
122
0
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(129 citation statements)
references
References 46 publications
3
122
0
2
Order By: Relevance
“…8,9,38,39 Excess gestational weight gain has consistently been shown to increase postpartum weight retention in the short term, 38,[40][41][42] and has also been associated with increased weight gain in the long term. 5,9 Because of the changes occurring in many developing countries due to the nutrition transition (described below), these same mechanisms may now be operating in some developing countries. For example, a recent Brazilian study found that women who had gestational weight gain above recommendations had significantly higher postpartum weight retention at 9 months than women who gained within or below the guidelines, independent of prepregnant BMI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9,38,39 Excess gestational weight gain has consistently been shown to increase postpartum weight retention in the short term, 38,[40][41][42] and has also been associated with increased weight gain in the long term. 5,9 Because of the changes occurring in many developing countries due to the nutrition transition (described below), these same mechanisms may now be operating in some developing countries. For example, a recent Brazilian study found that women who had gestational weight gain above recommendations had significantly higher postpartum weight retention at 9 months than women who gained within or below the guidelines, independent of prepregnant BMI.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] Excessive gestational weight gain and the inability to lose this weight in the postpartum period are thought to be two of the main ways in which reproduction contributes to overweight. 4,5,[8][9][10] In developing countries, frequent reproductive cycles (especially when accompanied by short or absent recuperative intervals, that is periods free from pregnancy or breastfeeding) have been suggested as a risk factor for maternal depletion. 11 Poor dietary intake and heavy activity patterns further exacerbate the nutritional and energetic stress of frequent reproductive cycles, such that nutritional status deteriorates over time.…”
Section: Introductionmentioning
confidence: 99%
“…If women gain weight during pregnancy according to the Institute of Medicine (IOM) recommendations, but fail to lose the extra weight by 6 months postpartum, they experience long term weight increases (Rooney & Schauberger, 2002). In addition, pre-pregnant body mass index (BMI) has also been shown to contribute to long term obesity, because women who start pregnancy heavier retain more weight following childbirth (Gunderson et al, 2004;Linne, Dye, Barkeling, & Rossner, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…11,27 Few strong predictive factors before and during pregnancy have been identified, although weight retention at 1 year after delivery has been identified previously as a good point of predicting further weight development. 28 Clinically there is a need for reference values for high weight gain during pregnancy in order to identify women at risk of subsequent adverse weight development. Such reference values could enable targeted intervention during and after this major life event to prevent pregnancy to become a trigger of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…34 To analyse the implications of drop-outs, we have made several drop-out analyses to determine if our material is representative. 28 It is known from previous studies that the subjects who drop out usually are people with low income and low socio-economic status. 39 These variables also correlate with higher body weight.…”
Section: Discussionmentioning
confidence: 99%